2020
DOI: 10.2147/ppa.s265503
|View full text |Cite
|
Sign up to set email alerts
|

<p>Choosing and Using the Progesterone Vaginal Ring: Women’s Lived Experiences in Three African Cities</p>

Abstract: This study explored experiences of selecting and utilizing a newly introduced contraceptive-the progesterone vaginal ring (PVR)-among women seeking a contraceptive method in 3 African capital cities (Abuja, Nairobi, and Senegal). The study explored women's perceptions of, and lived experiences with, using the new product to better understand their reception of a new contraceptive. This understanding will help inform the design of programs to support women in their adoption and continued use of the PVR and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This was consistent with previous findings regarding the views of women about the method. 2 , 12 Such positive views might contribute to men’s support for their partners to use the method, and thus improve the SRH and rights of women in the study settings. The finding further suggests that husbands could play an important role in promoting PVR if they find the method acceptable, and thus contribute to expanding the SRH and rights of women generally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was consistent with previous findings regarding the views of women about the method. 2 , 12 Such positive views might contribute to men’s support for their partners to use the method, and thus improve the SRH and rights of women in the study settings. The finding further suggests that husbands could play an important role in promoting PVR if they find the method acceptable, and thus contribute to expanding the SRH and rights of women generally.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this view may negate the goal of achieving SRH and rights for women through self-use products such as PVR, a previous study showed that women were also of the view that they needed to inform their partners to ensure harmony in the home. 12 In patriarchal societies such as the study settings, men’s views and perspectives often shape the choices available to women, women’s decision-making, women’s own formation of opinions, and women’s behaviours. 20 , 21 The social position of men in the study communities suggests that their support is crucial for enhancing women’s sustainable use of PVR given the considerable influence they have on the SRH and rights of women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns about device use have been mirrored in a study about the SILCS Diaphragm in South Africa, in which it was also highlighted that education and information dissemination could address concerns about the physical properties of the device [ 24 , 25 ]. Studies on vaginal rings have also demonstrated the importance of comfort and partner acceptability with use, and especially the impact on sex [ 28 , 29 ]. Additionally, previous studies suggest that women have regularly been underestimated in their ability to care for and wear cervical barrier devices such as diaphragms appropriately [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst increasing choice remains crucial, efficient uptake of existing and new vaginal rings requires an in-depth understanding of user preferences, and barriers and facilitators to acceptability and adherence (8,(14)(15)(16)(17)(18)(19)(20). Multipurpose prevention technologies (MPTs) targeting combination(s) of HIV, other STIs, and unintended pregnancy are currently under development.…”
Section: Introductionmentioning
confidence: 99%